Astragaloside IV attenuates high glucose-induced EMT by inhibiting the TGF-β/Smad pathway in renal proximal tubular epithelial cells. Issue 6 (23rd June 2020) - Wang, Ya-Ning; Zhao, Shi-Li; Su, Yan-Yan; Feng, Jun-Xia; Wang, Shuai; Liao, Xiao-Ming; Wang, Li-Na; Li, Jing-Chun; Meng, Ping; Li, Hong-Yan; Zhang, Yun-Fang
Abstract: In the present study, we examined the molecular mechanism of astragaloside IV (AS-IV) in high glucose (HG)-induced epithelial-to-mesenchymal transition (EMT) in renal proximal tubular epithelial cells (PTCs). NRK-52E cell viability and apoptosis were determined by the cell counting kit-8 (CCK-8) assay and flow cytometric analysis, respectively. Expressions of E-cadherin, N-cadherin, vimentin, and occludin were measured by Western blot, and those of E-cadherin and N-cadherin were additionally measured by immunofluorescence analysis. Transforming growth factor-β1 (TGF-β1) and α-smooth muscle actin (α-SMA) expressions were detected by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot. The expressions of Smad2, Smad3, phosphorylated-Smad2 (p-Smad2), and p-Smad3 were measured using Western blot. We found that AS-IV could recover NRK-52E cell viability and inhibit HG-induced cell apoptosis. TGF-β1, α-SMA, Smad2, Smad3, p-Smad2, and p-Smad3 expressions were decreased in the AS-IV-treated groups compared with the HG group. Moreover, the expressions of E-cadherin and occludin were remarkably up-regulated and those of N-cadherin and vimentin were down-regulated in the AS-IV-treated groups compared with the HG group. Interestingly, the TGF-β1 activator SRI-011381 hydrochloride had an antagonistic effect to AS-IV on HG-induced EMT behavior. In conclusion, AS-IV attenuates HG-induced EMT by inhibiting the TGF-β/Smad pathway in renal PTCs.